The financial strategies and approaches of Chinese government towards the internationalization of higher education in China - Frank Okai Larbi; Zaoming Ma; Xianzhe Chen; Yating Hu (Amfiteatru Economic Journal, 2020)
Approaches of internationalization of higher education (HE) have stimulated numerous countries to concurrently formulating innovative policies and strategies to make their higher educational institutions (HEIs) globally competitive. This has the aim to attract more international students and talents. In the view of this, many countries adopt different approaches to internationalize their HEIs. It is of this background the study has explored how the Chinese government's strategy and approaches boost up the attraction of international students to Chinese HE and to augment their internationalization practices. The study adopted qualitative research methodology, specifically employed interview and document analysis. Fifteen students were interviewed from three universities in Beijing. The study showed the role of the Chinese government and their strategies through scholarship provision and other programs to beef up the internationalization of Chinese HEIs. The study concluded by recommending that the HEIs should pay much attention to the quality education to international students not only been enthused with the quantitative nature of internationalization.
Keywords: A2; H52; I23; 330; internationalization; higher education; China; strategies; approaches